Effects of attribute-based regulation on technology adoption: The case of feed-in tariffs for solar photovoltaic - Robert Germeshausen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Feed-in tariffs are a widespread policy instrument to support the diffusion of renewable energy technologies. I investigate the impact of the size-based differentiation of these tariffs on the adoption of residential scale solar photovoltaic (PV) installations in Germany. Exploiting a policy change of administrative size classes for PV systems, I find that (i) the reduction in marginal feed-in tariffs decreases new capacity additions by around 29 per cent, and (ii) differentiated tariffs provide incentives for excess bunching at the ceiling of the smaller size class. Excess bunching decreases newly installed PV capacity additionally by around 14 per cent. Back-of-the-envelope calculations suggest that this may lead to annual efficiency losses that increase over time from about 0.2 to 4.4 per cent of the annual support cost for new small PV installations.
Keywords: O38; Q42; Q48; 330; solar photovoltaic; feed-in tariffs; diffusion of renewable energy technologies; attribute-based regulation; bunching analysis